SYSTEMATIC REVIEW ON THE EFFECTIVENESS OF HIGH-FLOW NASAL CANNULA IN THE TREATMENT OF ACUTE RESPIRATORY FAILURE DUE TO BRONCHIOLITIS IN CHILDREN (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize current evidence on the effectiveness of High-Flow Nasal Cannula (HFNC) oxygen therapy in the management of respiratory failure caused by bronchiolitis in children.Methods: This review analyzed 55 studies evaluating the clinical outcomes of HFNC therapy in children under two years of age with bronchiolitis-associated respiratory failure. Data were retrieved from online databases up to June 30, 2025.Results: Most studies on HFNC in bronchiolitis were observational (69.1%), focusing on children under 24 months (96.4%) with moderate to severe disease (70.9%), and were primarily conducted in pediatric intensive care units (38.2%). However, inconsistency in failure definitions and lack of standardized treatment protocols limited cross-study comparability. Overall, HFNC demonstrated high efficacy and safety, with approximately 70% of studies reporting a success rate ≥70%, a very low mortality rate (0.2%; 19/24 studies reported no deaths), and rare serious complications (
Keywords: high-flow nasal cannula; respiratory failure; bronchiolitis; children.